(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
This article covers the issues of choosing the types and methods of marketing research in the diversification of the company’s activities. Ways to choose and correctly apply the types and methods of marketing research in studying the market environment and diversifying the company’s activities are shown.